Tingkat Homework Management di Lembaga Pendidikan Islam: Studi Deskriptif Kuantitatif Siswa MTs di Kota Bandung - Nasrudin, Ega; Islamy, Mohammad Rindu Fajar; Anwar, Saepul (J-PAI: Jurnal Pendidikan Agama Islam, 2023)
Homework is one strategy to increase students' knowledge outside of intracurricular or extracurricular hours. However, unfortunately, the current phenomenon shows that homework is thought to have negative impacts such as the emergence of academic burnout or academic procrastination. This research aims to describe the quality of students' homework management in Islamic educational institutions. This research uses a quantitative descriptive approach. Data was collected via closed questionnaire with a sample of 345 students from a total population of 762 students. The location of this research is at one of the MTs in Bandung City. The results of this research reveal that the quality of students' homework management is on average at a high level. The highest indicator in this case is the indicator of emotional conditioning. These indicators are then followed by indicators for creating a conducive environment, indicators for the ability to manage time well, indicators for the motivation aspect, and indicators for the ability to overcome disturbances. This research also shows that students' ability to avoid distractions needs to be improved.